2012
DOI: 10.1007/s10195-012-0212-0
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Max Page muscle sliding operation for the treatment of Volkmann’s ischemic contracture of the forearm

Abstract: BackgroundVolkmann’s ischemic contracture is a less common but crippling condition affecting the extremities. Once the condition sets in, the prognosis always remains guarded, even after long and intensive physiotherapy and various restorative surgical techniques. This study was undertaken to evaluate the long-term functional results of the Max Page muscle slide operation in patients with Volkmann’s ischemic contracture of the forearm of moderate degree (Tsuge classification).Materials and methodsNineteen pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Meena et al 7 from Iran reported 8.3 years as the average age of their patients. 6 In this study, a significant proportion of patients developed VICs following their treatment for forearm fractures by traditional bone setters in the rural locales. In all these cases, tight constricting bandages had been fashioned with locally available bamboo sticks (Figure 1).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Meena et al 7 from Iran reported 8.3 years as the average age of their patients. 6 In this study, a significant proportion of patients developed VICs following their treatment for forearm fractures by traditional bone setters in the rural locales. In all these cases, tight constricting bandages had been fashioned with locally available bamboo sticks (Figure 1).…”
Section: Discussionmentioning
confidence: 75%
“…Approximately 20% of these fractures are associated with some form of vascular compromise. 6,[12][13][14] Electric burns constituted the second most common group of patients with VICs in the current study. We are faced with the menace of burns particularly the high voltage ones, which have many long term repercussions including VICs.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Because of the extent of muscle degeneration, and even if the deformity can be improved using flexor tendon lengthening or muscle sliding, the grip strength is expected to be markedly decreased and in particular the power of flexion of the distal IPJ. In a review of 19 patients, performed by Shama and Swamy, 19 most patients (14 cases) were able to achieve grip strengths in the good range (within ≥ 75% of the normal limb). However, preoperatively, most patients like in this report, are unable to perform the test due to the deformity, and poor grip was already present.…”
Section: Discussionmentioning
confidence: 99%